SURVEY OF STOMOXYS SPP. FLIES INFESTATION ON BALI CATTLE IN BADUNG REGENCY - Lalupada, Dhea Septiany Peda; Dwinata, I Made; Oka, Ida Bagus Made (Buletin Veteriner Udayana, 2021)
Bali cattle are a lot of livestock raised by people in Badung Regency. Stomoxys spp. Flies is one of the blood-sucking ectoparasites and also acts as a vector of several diseases such as Rickettsia ( anaplasma marginale ), surra ( trypanosoma evansi ), besnoitiosis ( besnoitia besnoiti ). Factors that can affect the presence of Stomoxys spp. in cattle including maintenance, regional conditions and gender. This study aims to determine the prevalence of Stomoxys spp. in Bali cattle in Badung Regency, as well as the relationship between how to maintain, the condition of the region, gender and age of Stomoxys spp . The research sample was determined purposively with a sample of 300 Bali cattle. This study was an observational study with a cross-sectional design. The results showed that the prevalence of Stomoxys spp . in Badung Regency is 50.3%. The prevalence of Stomoxys spp . on stranded livestock (59%) higher infestation by Stmoxys spp . compared to tied cattle (33%), while in wetland areas (59%) the prevalence is higher than dryland areas (33%). The highest prevalence of young livestock (51.4%) was infested by Stomoxys spp. compared to adult cattle (50%) and old livestock (45.5%), the prevalence of Stomoxys spp. in female cattle (58.1%) higher than male cattle (35.3%). Factors in area conditions, maintenance methods and sex were very influential (P <0.05) on Stomoxys spp . in Bali cattle in Badung Regency, but age has no effect (P> 0.05).